All-solid-state battery
Patent Information
- Application Number
- CN201980019904.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-03-19
- Filing Date
- 2019-03-19
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2039-03-19
AI Technical Summary
另外,难以将硫化物固体电解质进行片材化
[0040] According to the present invention, an all-solid-state battery with relatively high self-discharge characteristics can be provided.
Smart Images

Figure CN111868991B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an all-solid-state battery. This application claims priority based on Japanese Patent Application No. 2018-051192 filed on March 19, 2018, and the contents thereof are incorporated herein by reference. Background Art
[0002] In recent years, lithium-ion secondary batteries have been widely used as power sources for mobile communication devices such as mobile phones and smart phones, laptops, tablet PCs, and portable small devices such as game consoles. The lithium-ion secondary batteries used in such portable small devices require miniaturization, thinning, and improved reliability. In order to drive these electronic devices for a long time, research and development of lithium-ion secondary batteries with long life and high capacity are actively underway.
[0003] As lithium-ion secondary batteries, batteries using organic electrolytes and batteries using solid electrolytes are known. Lithium-ion secondary batteries using organic electrolytes in electrolytes have always been formed by having a positive electrode and a negative electrode coated with a positive electrode active material or a negative electrode active material that absorbs and releases lithium ions on both sides of a sheet-shaped current collector such as aluminum or copper, sandwiching a separator between the positive and negative electrodes and winding them multiple times to form a winding body, and sealing it together with the electrolyte in an outer body of a cylindrical, square, button-shaped, etc.
[0004] In such lithium-ion secondary batteries, the electrolyte contains a flammable organic solvent. Therefore, leakage or short circuit may occur due to impact, which may cause abnormal heating. Therefore, a battery with better safety is desired.
[0005] As for lithium-ion secondary batteries (all-solid-state batteries) using solid electrolytes as electrolytes, compared with lithium-ion secondary batteries using organic electrolytes, the freedom of design of battery shape is high, and the battery size is easy to be miniaturized and thinned. In addition, all-solid-state batteries do not contain electrolytes, so they have the advantages of high reliability, such as no leakage and abnormal heating.
[0006] All-solid batteries are mainly classified into two types: thin-film all-solid batteries and bulk all-solid batteries. Thin-film all-solid batteries are made using thin-film technologies such as PVD or sol-gel methods. Bulk all-solid batteries are made by powder molding of electrode active materials or sulfide-based solid electrolytes.
[0007] Thin-film all-solid-state batteries have a low capacity because it is difficult to increase the thickness or stack the active material layers. In addition, thin-film all-solid-state batteries have a high manufacturing cost.
[0008] The bulk type all-solid battery uses a sulfide solid electrolyte. When the sulfide solid electrolyte layer reacts with water, hydrogen sulfide is produced. Therefore, the bulk type all-solid secondary battery needs to be made in a glove box that manages the dew point. In addition, it is difficult to make the sulfide solid electrolyte into sheets. Therefore, it is difficult to make the solid electrolyte layer thinner and stack the battery higher in the bulk type all-solid battery.
[0009] Patent Documents 1 and 2 disclose methods for manufacturing industrially applicable all-solid batteries that have been completed in view of the above circumstances. The methods for manufacturing all-solid batteries disclosed in Patent Documents 1 and 2 are as follows: each component is formed into sheets using an oxide-based solid electrolyte that is stable in air, and then stacked and fired simultaneously.
[0010] Specifically, the manufacturing method of the all-solid-state battery described in Patent Document 1 discloses the following method: an electrode layer sheet and a solid electrolyte sheet are stacked and fired, and then heated at 100°C to remove moisture to produce a fired laminate. Next, a polymethyl methacrylate resin gel compound is applied to a metal lithium plate, the coated surface is attached to the surface of the solid electrolyte layer side of the fired laminate, and a 2032-type button cell is used to seal the laminate to produce an all-solid-state battery.
[0011] Patent document 2 discloses a method for producing an all-solid-state battery having a stacked structure having, in order from the plane of paper, a positive electrode collector, a positive electrode, a portion of a solid electrolyte layer, a solid electrolyte layer, a solid electrolyte layer and negative electrode, and a negative electrode collector.
[0012] Prior art literature
[0013] Patent Literature
[0014] Patent Document 1: Japanese Patent Application No. 2012-534547 (Japanese Patent Application No. 2013-508577)
[0015] Patent Document 2: Japanese Patent Application Publication No. 2016-66550 Summary of the invention
[0016] Technical problem to be solved by the invention
[0017] However, the all-solid battery described in Patent Document 1 cannot function effectively when moisture invades, so an attempt is made to use a 2032-type button battery to reduce the invasion of moisture. However, there is moisture contained in the atmosphere at the time of sealing or moisture contained in the polymethyl methacrylate resin gel inside the seal. In addition, since the 2032-type button battery sealing material itself is not dehumidified, moisture will also exist inside the seal. That is, the all-solid battery shown in Patent Document 1 may react with components in the atmosphere (mainly moisture) in the positive electrode layer or the negative electrode layer after charging, and cause self-discharge.
[0018] The all-solid-state battery disclosed in Patent Document 2 may also cause self-discharge in the same manner. That is, the all-solid-state batteries disclosed in Patent Documents 1 and 2 have insufficient self-discharge characteristics.
[0019] The present invention has been developed in view of the above-mentioned technical problems, and its object is to provide an all-solid-state battery with high self-discharge characteristics.
[0020] Solutions for solving technical problems
[0021] One embodiment of the present invention provides an all-solid-state battery, comprising: a positive electrode layer, comprising a positive electrode current collector layer and a positive electrode active material layer disposed on the positive electrode current collector layer; a negative electrode layer, comprising a negative electrode current collector layer and a negative electrode active material layer disposed on the negative electrode current collector layer; a solid electrolyte layer, which is disposed between the positive electrode layer and the negative electrode layer and has a solid electrolyte, wherein the all-solid-state battery comprises a power storage portion and an outer casing portion, wherein the positive electrode layer and the negative electrode layer are opposed to each other via the solid electrolyte layer, and the ion conductivity of the outer casing portion is 10 -2 S / cm or less.
[0022] According to the structure, by setting it as a structure with an outer casing, the chance of the positive electrode active material layer or the negative electrode active material layer in a charged state being exposed to components in the atmosphere (mainly water) is reduced, thereby suppressing the generation of energy consumed when reacting with components in the atmosphere.
[0023] In addition, by setting the ion conductivity of the outer casing to 10 -2 S / cm or less, thereby reducing the bias of lithium ions in the outer casing during charging. As a result, the leakage current caused by the relaxation of the bias of lithium ions in the outer casing can be suppressed in the open circuit state after charging. As a result, the self-discharge characteristics can be improved.
[0024] The self-discharge rate of the all-solid-state battery is preferably 6.5% or less, more preferably 6% or less, and even more preferably 5% or less.
[0025] In the all-solid battery of the above aspect, the ratio of the ionic conductivity of the outer casing to the ionic conductivity of the solid electrolyte layer, Y(ionic conductivity of the outer casing) / (ionic conductivity of the solid electrolyte layer), may be Y≤1.
[0026] According to the above structure, by making the ratio of the ion conductivity of the outer casing to the ion conductivity of the solid electrolyte layer Y (ion conductivity of the outer casing) / (ion conductivity of the solid electrolyte layer) Y≤1, charging can be completed before the bias of the lithium ions in the outer casing becomes larger during charging, and the bias of the lithium ions in the outer casing can be reduced. As a result, the leakage current caused by the relaxation of the bias of the lithium ions in the outer casing can be further suppressed in the open circuit state after charging, and the self-discharge characteristics can be further improved.
[0027] In the all-solid battery of the above embodiment, the ion conductivity ratio Y(ion conductivity of the outer casing) / (ion conductivity of the solid electrolyte layer) of the ion conductivity of the outer casing and the ion conductivity of the solid electrolyte layer may be 0≤Y≤1.
[0028] According to the above structure, by setting the ratio of the ion conductivity of the outer casing to the ion conductivity of the solid electrolyte layer constituting the power storage part to 0≤Y≤1, the charging can be completed before the bias of the lithium ions in the outer casing becomes larger, and the bias of the lithium ions in the outer casing can be further reduced. As a result, the leakage current caused by the relaxation of the bias of the lithium ions in the outer casing can be further suppressed in the open circuit state after charging, and the self-discharge characteristics can be further improved.
[0029] In the all-solid battery of the above embodiment, the ionic conductivity ratio Y (ionic conductivity of the outer casing) / (ionic conductivity of the solid electrolyte layer) of the ionic conductivity of the outer casing to the ionic conductivity of the solid electrolyte layer may be 10 -6 ≤Y≤1.
[0030] According to the above configuration, the ratio of the ion conductivity of the exterior portion to the ion conductivity of the solid electrolyte layer constituting the power storage portion is set to 10. -6 ≤Y≤1, the structure of the all-solid-state battery can further complete the charging before the bias of the lithium ions in the outer packaging becomes larger, and can further reduce the bias of the lithium ions in the outer packaging. As a result, the leakage current caused by the relaxation of the bias of the lithium ions in the outer packaging can be further suppressed in the open circuit state after charging, and the self-discharge characteristics can be further improved.
[0031] In the all-solid-state battery of the above aspect, the exterior portion may be configured as at least a portion of the all-solid-state battery other than the power storage portion.
[0032] According to the above structure, by providing an outer casing in at least a part of the all-solid-state battery except the power storage part, the chance of the positive electrode active material layer or the negative electrode active material layer in the charged state being exposed to components in the atmosphere (mainly water) can be further reduced, and the bias of lithium ions in the outer casing during charging can be further reduced. By doing so, the self-discharge characteristics can be further improved.
[0033] In the all-solid-state battery of the above aspect, the outer casing may be at least one selected from oxides, alloy oxides, phosphates, sulfides, polyanion compounds, and glass.
[0034] According to the above structure, the bias of lithium ions in the outer packaging part can be suppressed, and a good connection between the outer packaging part and the power storage part can be constructed, cracks caused by poor connection can be suppressed, and the intrusion of components in the atmosphere from the cracks can be suppressed, and the energy consumed when the positive electrode active material layer or the negative electrode active material layer reacts with components in the atmosphere can be suppressed. Thus, the self-discharge characteristics can be further improved.
[0035] The electronic conductivity of the outer casing of the all-solid-state battery of the above embodiment may be 10 -9 S / cm or less.
[0036] According to the above structure, while suppressing the bias of lithium ions in the outer casing and generating an open circuit potential difference during charging, discharging, or after charging, the outer casing can also maintain a good electronic insulation state and suppress the short circuit between the outer casing and the power storage unit. Thus, the self-discharge characteristics can be further improved.
[0037] The porosity P of the outer packaging portion of the all-solid-state battery of the above embodiment may be 0.4 or less.
[0038] According to the above configuration, by setting the porosity of the outer casing to be within the above range, it is possible to suppress the deflection of lithium ions in the outer casing and to establish a better bond with the electric storage element.
[0039] Effects of the Invention
[0040] According to the present invention, an all-solid-state battery having high self-discharge characteristics can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a schematic cross-sectional view schematically showing an example of an all-solid-state battery according to one embodiment of the present invention.
[0042] Figure 2 This is a schematic cross-sectional view schematically showing an example of an all-solid-state battery according to one embodiment of the present invention.
[0043] Figure 3 It is a cross-sectional schematic diagram schematically showing an example of a power storage unit according to an embodiment of the present invention.
[0044] Explanation of symbols
[0045] 50: All-solid-state battery
[0046] 51: Exterior Department
[0047] 52: Positive electrode collector layer
[0048] 53: Positive electrode active material layer
[0049] 54: Negative electrode collector layer
[0050] 55: Negative electrode active material layer
[0051] 56: Solid electrolyte layer
[0052] 57: Terminal electrode
[0053] 60: All-solid-state battery
[0054] 61: Exterior Department
[0055] 62: Positive electrode collector layer
[0056] 63: Positive electrode active material layer
[0057] 64: Negative electrode collector layer
[0058] 65: Negative electrode active material layer
[0059] 66: Solid electrolyte layer
[0060] 67: Terminal electrode
[0061] 10: Power storage unit
[0062] 11: Positive electrode collector layer
[0063] 12: Positive electrode active material layer
[0064] 13: Negative electrode collector layer
[0065] 14: Negative electrode active material layer
[0066] 15: Solid electrolyte layer DETAILED DESCRIPTION
[0067] Hereinafter, the preferred examples of the embodiments of the all-solid-state battery and the power storage unit of the present invention will be described in detail with reference to the accompanying drawings. The accompanying drawings used in the following description are for the sake of convenience in order to easily understand the features of the present embodiment, and sometimes the enlarged representation of the features is used, and the dimensional ratio of each component is sometimes different from the actual. The materials, dimensions, etc. exemplified in the following description are one example, and the present invention is not limited to these, and can be implemented by appropriate changes within the scope of not changing its purpose. That is, the present invention is not only limited to the embodiments shown below, but can be implemented by appropriate changes within the scope of achieving its effect. For example, numbers, numerical values, amounts, ratios, shapes, positions, characteristics, etc. can be omitted, added or changed within the scope of not departing from the main purpose of the present invention.
[0068] Below, refer to Figure 1 A preferred example of the all-solid-state battery according to the first embodiment will be described.
[0069] Figure 1 This is a schematic cross-sectional view schematically showing a cross section of an example of the all-solid-state battery according to the first embodiment. Figure 1 The all-solid battery 50 shown has an outer casing 51, a positive electrode collector layer 52, a positive electrode active material layer 53, a negative electrode collector layer 54, a negative electrode active material layer 55, a solid electrolyte layer 56, and a terminal electrode 57. The all-solid battery 50 has a structure in which the positive electrode collector layer 52, the positive electrode active material layer 53, the negative electrode collector layer 54, the negative electrode active material layer 55, and the solid electrolyte layer 56 are stacked, and has one or more power storage units. The outer casing 51 is configured to cover the power storage unit other than the portion connected to the terminal electrode 57.
[0070] Figure 1 In the all-solid battery 50 shown, for convenience, each of the positive electrode collector layers 52 is sometimes referred to as positive electrode active material 52c, 52b, and 52a in order according to the stacking direction. Similarly, each of the positive electrode active material layers 53 is sometimes referred to as 53c2, 53c1, 53b2, 53b1, and 53a1, each of the negative electrode collector layers 54 is sometimes referred to as 54a, 54b, and 54c, and each of the positive electrode active material layers 55 is sometimes referred to as 55a1, 55a2, 55b1, 55b2, 55c1, and 55c2. In addition, the positive electrode collector layer 52 and the positive electrode active material layer 53 arranged on one or both sides of the main surface thereof are sometimes collectively referred to as a positive electrode layer 523. For convenience, each of the positive electrode layers 523 is referred to as a positive electrode layer 523c, 523b, and 523a in the stacking direction. Similarly, the negative electrode current collector layer 55 and the negative electrode active material layer 54 disposed on one or both sides of the main surface thereof are sometimes collectively referred to as the negative electrode layer 545. The respective orientations of the negative electrode layer 545 in the stacking direction are sometimes designated as 545a, 545b, and 545c. The outermost portion of the power storage portion of the all-solid-state battery 50 is formed by the positive electrode current collector layer 52a and the negative electrode current collector layer 54a.
[0071] In addition, an intermediate layer for relaxing the thermal expansion coefficient may be provided between at least one of the positive electrode active material layer 53 and the solid electrolyte layer 56 and between the negative electrode active material layer 55 and the solid electrolyte layer 56 .
[0072] The positive electrode active material layer 53 is provided on at least one side of the main surface of the positive electrode current collector layer 52, and may be provided on both sides. Figure 1 In the embodiment, the positive electrode active material layer 53a is provided on one side of the main surface of the positive electrode collector layer 52a, and the positive electrode active material layers 53b1 and 53b2 are provided on both main surfaces of the positive electrode active material layer 52b.
[0073] The negative electrode active material layer 55 is provided on at least one side of the negative electrode current collector layer 54, and may also be provided on both sides. Figure 1 In the embodiment, the positive electrode active material layer 55a is provided on one side of the main surface of the positive electrode collector layer 54a, and the positive electrode active material layers 55b1 and 55b2 are provided on both main surfaces of the positive electrode active material layer 54b.
[0074] Each positive electrode collector layer 52 and each negative electrode collector layer 54 are connected to different terminal electrodes 57. By connecting the positive electrode collector layer 52 to the terminal electrode 57 and connecting the negative electrode collector layer 54 to the terminal electrode 57, the all-solid-state battery 50 can be electrically connected to the outside.
[0075] in addition, Figure 2 : is a schematic cross-sectional view schematically showing a cross section of an example of a solid-state battery according to the second embodiment. Figure 2 As shown, the all-solid battery 60 includes: an outer package 61, a positive electrode collector layer 62, a positive electrode active material layer 63, a negative electrode collector layer 64, a negative electrode active material layer 65, a solid electrolyte layer 66, and a terminal electrode 67. The all-solid battery 60 includes: an outer package 61, a positive electrode collector layer 62, a positive electrode active material layer 63, a negative electrode collector layer 64, a negative electrode active material layer 65, a solid electrolyte layer 66, and a terminal electrode 67. The all-solid battery 60 is a structure in which the positive electrode collector layer 62, the positive electrode active material layer 63, the negative electrode collector layer 64, the negative electrode active material layer 65, and the solid electrolyte layer 66 are stacked separately, and has more than one power storage unit. The outermost part of the power storage unit in the all-solid battery 60 is composed of a positive electrode active material layer 63a and a negative electrode active material layer 65a. The outer package 61 is configured to cover the power storage unit other than the part connected to the terminal 67.
[0076] In addition, an intermediate layer for relaxing the thermal expansion coefficient may be provided between at least one of the positive electrode active material layer 63 and the solid electrolyte 66 and between the negative electrode active material layer 65 and the solid electrolyte 66 .
[0077] Each positive electrode current collector layer 62 and each negative electrode current collector layer 64 are connected to different terminal electrodes 67. This structure enables electrical connection to the outside.
[0078] Figure 3 1 is a cross-sectional view showing an example of a power storage unit according to this embodiment. Figure 3 As shown, the power storage unit 10 includes a positive electrode collector layer 11 , a positive electrode active material layer 12 , a negative electrode collector layer 13 , a negative electrode active material layer 14 , and a solid electrolyte layer 15 , and each of these layers is stacked.
[0079] In the present embodiment, the all-solid-state battery 50 is preferably an all-solid-state battery having a power storage unit and an outer packaging unit, wherein the power storage unit comprises: a positive electrode layer composed of a positive electrode collector layer 52 and a positive electrode active material layer 53 disposed on the positive electrode collector layer 52, a negative electrode layer composed of a negative electrode collector layer 54 and a negative electrode active material layer 55 disposed on the negative electrode collector layer 54, and a solid electrolyte layer 56 disposed between the positive electrode layer and the negative electrode layer and having a solid electrolyte, and the ion conductivity of the outer packaging unit is 10 -2 S / cm or less.
[0080] According to the above structure, the chance of positive electrode active material layer 53 or negative electrode active material layer 55 being exposed to components (mainly water) in the atmosphere in a charged state is reduced by having the outer casing 51. That is, the energy consumed when reacting with components in the atmosphere can be suppressed.
[0081] In addition, by setting the ionic conductivity to 10 -2 The outer casing 51 with a density of less than 100 S / cm can reduce the bias of lithium ions in the outer casing 51 during charging. As a result, leakage current caused by the relaxation of the bias of lithium ions in the outer casing 51 can be suppressed in the open circuit state after charging. This can improve the self-discharge characteristics.
[0082] In this embodiment, the ratio Y(ionic conductivity of the outer casing 51) / (ionic conductivity of the solid electrolyte layer) of the all-solid battery 50 to the ionic conductivity of the solid electrolyte layer 56 is preferably Y≤1.
[0083] According to the above structure, by setting the ratio Y (ion conductivity of the outer casing 51) / (ion conductivity of the solid electrolyte layer 56) of the ion conductivity of the outer casing 51 to that of the ion conductivity of the solid electrolyte layer 56 to be within this range, charging can be completed before the bias of the lithium ions in the outer casing 51 during charging becomes larger. That is, the bias of the lithium ions in the outer casing 51 can be reduced. As a result, the leakage current caused by the relaxation of the bias of the lithium ions in the outer casing 51 can be further suppressed in the open circuit state after charging, and the self-discharge characteristics can be further improved.
[0084] In the present embodiment, the ratio Y (ionic conductivity of the outer casing 51) / (ionic conductivity of the solid electrolyte layer) of the all-solid battery 50 is preferably 0 ≤ Y ≤ 1. In addition, the ratio Y of the ionic conductivity of the outer casing 51 to the ionic conductivity of the solid electrolyte layer 56 is more preferably 10 -6 ≤Y≤1. In addition, it is more preferred that the ratio Y of the ion conductivity of the outer casing 51 to the ion conductivity of the solid electrolyte layer 56 is 10 -6 ≤Y≤10 -2.
[0085] According to the above-mentioned structure, by setting the ratio of the ion conductivity of the outer casing 51 to the ion conductivity of the solid electrolyte layer 56 constituting the power storage unit to be within the range, the charging can be completed before the bias of the lithium ions in the outer casing 51 becomes larger, and the bias of the lithium ions in the outer casing 51 can be further reduced. As a result, the leakage current caused by the relaxation of the bias of the lithium ions in the outer casing 51 can be further suppressed in the open circuit state after charging, and the self-discharge characteristics can be further improved.
[0086] In the all-solid-state battery 50 of the present embodiment, the exterior portion 51 is preferably configured as at least a portion other than the power storage portion.
[0087] According to the above structure, by providing the outer casing 51 in at least a part of the all-solid-state battery 50 other than the power storage part, the chance of the positive electrode active material layer 53 or the negative electrode active material layer 55 in the charged state being exposed to components (mainly water) in the atmosphere can be further reduced. In addition, the bias of lithium ions in the outer casing 51 during charging can be further reduced. By doing so, the self-discharge characteristics can be further improved.
[0088] In the present embodiment, in the all-solid-state battery 50 , the outer casing 51 is at least one selected from oxides, alloy oxides, phosphates, sulfides, polyanion compounds, and glass.
[0089] According to the above structure, the bias of lithium ions in the outer casing can be suppressed, and a good connection between the outer casing 51 and the storage part can be constructed. That is, by suppressing cracks caused by poor connection, and further reducing the chance of atmospheric components intruding from the cracks, and the positive electrode active material layer 53 or the negative electrode active material layer 55 being exposed to atmospheric components (mainly water), the generation of energy consumed when reacting with atmospheric components can be suppressed. As a result, the self-discharge characteristics can be further improved.
[0090] In this embodiment, the electronic conductivity of the outer casing 51 of the all-solid-state battery 50 is preferably 10 -9 S / cm or less, more preferably 10 -11 the following.
[0091] According to the above structure, while suppressing the bias of lithium ions in the outer casing 51 and generating an open circuit potential difference during charging and discharging or after charging, the outer casing 51 can be kept in an electronically good insulating state and a short circuit between the outer casing 51 and the power storage unit can be suppressed. Thus, the self-discharge characteristics can be further improved.
[0092] In the present embodiment, the porosity P of the exterior parts 51 and 61 is preferably 0.4 or less, and more preferably 0.2 or less.
[0093] In this specification, "porosity" means the ratio of the total area of the void portion to the total area of the outer packaging portion in the image of the cross section parallel to the stacking direction of the laminate. The void ratio represented in the embodiment is calculated by the following method. The cross section that appears when the laminate is cut and processed by a cross-section polisher (CP) parallel to the stacking direction is observed using a scanning electron microscope (SEM). 10 parts are observed in the cross section containing the outer packaging portion at 1000 times, and the void ratio is calculated using image processing software for each SEM image obtained. The outer packaging portion in the SEM image is extracted by trimming, converted into a monochrome image and binarized (binarization), the void portion is set to black, and the portion other than this is set to white and the number of pixels is calculated respectively. By adding the number of pixels of the void portion and the portion other than this, the pixels of the extracted outer packaging portion are calculated. Then, the void ratio P of the outer packaging portion is calculated by the following formula.
[0094] Porosity P of the outer casing = Number of pixels in the voids / (Number of pixels in the voids and outside the voids)
[0095] (Porosity Control)
[0096] The method for controlling the porosity is not particularly limited, but it can be controlled by controlling the type or particle size of the sintering aid, the amount thereof added, the type or particle size of the sintering inhibitor, the amount thereof added, the type or particle size of the pore-forming material, the amount thereof added, the molding density of the molded body, the firing conditions (heating rate or firing temperature, holding time, cooling rate, type or flow rate of gas), or a combination thereof.
[0097] According to the above structure, by setting the porosity of the outer casing 51, 61 to the range, the bias of lithium ions in the outer casing 51, 61 can be suppressed, and a better connection with the storage element can be constructed, so that the intrusion of components in the atmosphere from cracks caused by poor connection can be suppressed and the leakage current can be reduced. Thus, the self-discharge characteristics can be further improved.
[0098] In this embodiment, the all-solid-state battery 50 is preferably composed of a positive electrode layer composed of a positive electrode collector layer 52 and a positive electrode active material layer 53 arranged on the positive electrode collector layer 52, a negative electrode layer composed of a negative electrode collector layer 54 and a negative electrode active material layer 55 arranged on the negative electrode collector layer 54, a storage part formed by a solid electrolyte layer 56 arranged between the positive electrode layer and the negative electrode layer and having a solid electrolyte, and an outer packaging part 51 with a relative density of more than 80%, more preferably more than 90%.
[0099] According to the above-mentioned structure, by setting the relative density of the all-solid-state battery 50 to be within this range, it is possible to obtain an all-solid-state battery 50 with improved self-discharge characteristics and a long cycle life.
[0100] The composition of the positive electrode current collector layer 52 and the negative electrode current collector layer 54 is not particularly limited, and for example, in addition to the current collector material, they may contain a positive electrode active material or a negative electrode active material, a solid electrolyte, and a sintering aid at any ratio.
[0101] The composition of the positive electrode active material layer 53 and the negative electrode active material layer 55 is not particularly limited, but for example, a lithium ion conductive aid, a sintering aid, or a conductive aid may be included in addition to the positive electrode active material or the negative electrode active material.
[0102] The composition of the solid electrolyte layer 56 is not particularly limited, but for example, a sintering aid may be included in addition to the solid electrolyte.
[0103] The positive electrode active material and the negative electrode active material constituting the positive electrode active material layer 53 and the negative electrode active material layer 55 are compared using the potentials of their respective compounds. Specifically, the compound exhibiting a higher potential among the respective compounds can be used as the positive electrode active material, and the compound exhibiting a lower potential can be used as the negative electrode active material. In addition, the positive electrode active material layer 53 and the negative electrode active material layer 55 can also be composed of a single compound or a plurality of compounds.
[0104] (Solid Electrolyte)
[0105] As the solid electrolyte constituting the solid electrolyte layers 56, 66, and 15 of the all-solid battery of this embodiment, it is preferable to use a material having low electron conductivity and high lithium ion conductivity. Although not limited to these examples, for example, it is preferably selected from La 0.5 Li 0.5 TiO 3 Perovskite compounds such as Li 14 Zn(GeO 4 ) 4 LISICON compounds, Li 7 La 3 Zr 2 O 12 Garnet compounds, LiTi 2 (PO 4 ) 3 or LiGe 2 (PO 4 ) 3 、LiZr 2 (PO 4 ) 3 (monoclinic), LiZr 2 (PO 4) 3 (rhombohedral crystal), Li 1.5 Ca 0.5 Zr 1.5 (PO 4 ) 3 , Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 or Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 , Li 3 PO 4 or Li 3.5 Si 0.5 P 0.5 O 4 , Li 2.9 PO 3.3 N 0.46 Phosphorus oxides, Li 3.25 Ge 0.25 P 0.75 S 4 , Li 3 PS 4 Thio-LISICON (sulfide crystalline lithium superion conductor) type compounds, Li 2 SP 2 S 5 , Li 2 OV 2 O 5 -SiO 2 At least one of the glass compounds described above.
[0106] From the viewpoint of forming a thin and dense layer, the particle size of the solid electrolyte constituting the solid electrolyte layer of the all-solid-state battery of the present embodiment is preferably 0.05 μm to 5 μm or less, and more preferably 0.1 μm to 2.5 μm or less.
[0107] The thickness of the solid electrolyte layers 56 , 66 , and 16 is not particularly limited, but is preferably 0.1 to 100 μm, more preferably 0.3 to 20 μm, and even more preferably 0.6 to 10 μm from the viewpoint of maintaining self-discharge characteristics and achieving high-rate characteristics.
[0108] By setting the thickness of solid electrolyte layers 56 , 66 , and 16 to be within this range, the insulation of solid electrolyte layers 56 , 66 , and 16 can be maintained, and the movement distance of lithium ions during charge and discharge can be shortened, thereby reducing the internal resistance.
[0109] (Positive electrode active material)
[0110] The positive electrode active material contained in the positive electrode active material layers 53, 63, 12 and the positive electrode current collector layers 52, 62, 11 of this embodiment is preferably a lithium-containing compound such as lithium oxide, lithium sulfide, or an intercalation compound containing lithium, and two or more of them may be mixed for use. In particular, from the viewpoint of improving energy density, it is preferred to use a lithium-containing compound having the general formula Li x MO 2 The lithium composite oxide represented by , or the intercalation compound containing lithium is used as the positive electrode active material layer 53, 63, 12. In addition, M is preferably one or more transition metals, specifically, preferably at least one of Co, Ni, Mn, Fe, Al, V, and Ti. x varies depending on the charge and discharge state of the battery, and is usually a value in the range of 0.05≤x≤1.10. In addition, manganese spinel (LiMn) having a spinel crystal structure is used. 2 O 4 ), lithium iron phosphate (LiFePO 4 ) or LiCoPO 4 、LiNiPO 4 The like can also obtain a higher energy density and is therefore preferred.
[0111] Specifically, as the positive electrode active material constituting the positive electrode active material layer 53, 63, 12 of the all-solid-state battery 50, 60 and the storage unit 10, it is preferred to use a material that releases and adsorbs lithium ions efficiently. For example, it is preferred to use a transition metal oxide or a transition metal composite oxide. Specifically, it is preferred to use a lithium manganese composite oxide Li 2 Mn x3 Ma 1-x3 O 3 (0.8≤x3≤1, Ma=Co, Ni), lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), lithium manganese spinel (LiMn 2 O 4 ), and the general formula: LiNi x4 Co y4 Mn z4 O 2 (x4+y4+z4=1, 0≤x4≤1, 0≤y4≤1, 0≤z4≤1) represented by a composite metal oxide, a lithium vanadium compound (LiV 2 O 5 ), olivine-type LiMbPO 4 (wherein Mb is one or more elements selected from Co, Ni, Mn, Fe, Mg, Nb, Ti, Al, and Zr), lithium vanadium phosphate (Li 3 V 2 (PO4 ) 3 or LiVOPO 4 ), Li excess solid solution positive electrode Li 2 MnO 3 -LiMcO 2 (Mc=Mn, Co, Ni), lithium titanate (Li 4 Ti 5 O 12 ), with LiaNi x5 Co y5 Al z5 O 2 Any of the composite metal oxides represented by (0.9<a<1.3, 0.9<x5+y5+z5<1.1). In addition, the positive electrode active material constituting the positive electrode active material layers 53, 63, and 12 is not limited to these materials, and any material can be used as long as it is a positive electrode active material that electrochemically inserts and releases lithium ions.
[0112] From the viewpoint of forming a dense and thin positive electrode active material layer, the particle size of the positive electrode active material constituting the positive electrode active material layers 53 , 63 , and 12 of the present embodiment is preferably 0.05 μm to 5 μm, and more preferably 1 μm to 2.5 μm.
[0113] The thickness of the positive electrode active material layers 53, 63, and 12 is not particularly limited, but is preferably 0.1 to 100 μm, more preferably 0.3 to 10 μm, and further preferably 0.6 to 5 μm from the viewpoint of obtaining an all-solid-state battery with improved self-discharge characteristics and high capacity and high output.
[0114] (Negative electrode active material)
[0115] As the negative electrode active material contained in the negative electrode active material layers 55, 65, and 14 of the present embodiment, from the viewpoint of obtaining an all-solid battery with high weight energy density and volume energy density, it is preferred to use a material having a low potential relative to lithium and a large capacity per unit weight. Although not limited to these examples, for example, it is preferably at least one metal selected from Li, Sn, Si, Al, Ge, Sb, Ag, Ga, In, Fe, Co, Ni, Ti, Mn, Ca, Ba, La, Zr, Ce, Cu, Mg, Sr, Cr, Mo, Nb, V, and Zn, an alloy composed of two or more of these metals, an oxide or phosphate of the above metals, and an oxide or phosphate of the above alloy, or a material containing a carbon material.
[0116] From the viewpoint of forming a dense and thin negative electrode active material layer, the particle size of the negative electrode active material constituting the negative electrode active material layers 55 , 65 , and 14 of the present embodiment is preferably 0.05 μm to 5 μm, and more preferably 0.1 μm to 2.5 μm.
[0117] The thickness of the negative electrode active material layers 55, 65, and 14 is not particularly limited, but is preferably 0.1 to 100 μm, more preferably 0.5 to 10 μm, and further preferably 1 to 5 μm from the viewpoint of improving self-discharge characteristics and obtaining an all-solid-state battery with a higher capacity and a longer cycle life.
[0118] (Exterior materials)
[0119] As the outer casing material constituting the outer casing 51 and 61 of the all-solid battery of this embodiment, it is preferable to use an outer casing material having a low electron conductivity and a lithium ion conductivity lower than the lithium ion conductivity of the solid electrolyte constituting the solid electrolyte layer 56, 66, 15. Although not limited to these examples, it is preferable to select, for example, La 0.5 Li 0.5 TiO 3 Perovskite compounds such as Li 14 Zn(GeO 4 ) 4 LISICON compounds, Li 7 La 3 Zr 2 O 12 Garnet compounds, LiTi 2 (PO 4 ) 3 or LiGe 2 (PO 4 ) 3 、LiZr 2 (PO 4 ) 3 (monoclinic), LiZr 2 (PO 4 ) 3 (rhombohedral crystal), Li 1.5 Ca 0.5 Zr 1.5 (PO 4 ) 3 , Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 or Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 , Li3 PO 4 or Li 3.5 Si 0.5 P 0.5 O 4 or Li 2.9 PO 3.3 N 0.46 Phosphorus oxides, Li 3.25 Ge 0.25 P 0.75 S 4 or Li 3 PS 4 Thio-LISICON compounds, Li 2 SP 2 S 5 or Li 2 OV 2 O 5 -SiO 2 , glass compounds such as boric acid glass, silicate glass, borosilicate glass, ZrO 2 、Al 2 O 3 、SiO 2 At least one of the oxides of the above.
[0120] From the viewpoint of forming a dense layer, the particle size of the exterior material constituting the exterior of the all-solid-state battery of the present embodiment is preferably 0.05 μm to 5 μm, and more preferably 0.1 μm to 2.5 μm.
[0121] The thickness of the outer casing 51, 61 of the all-solid-state battery of this embodiment is not particularly limited, but is preferably 0.1 to 1000 μm, more preferably 1 to 500 μm, from the viewpoint of obtaining an all-solid-state battery that suppresses the intrusion of the atmosphere, improves the self-discharge characteristics, and has a longer cycle life.
[0122] (Conductive additive)
[0123] The positive electrode active material layer 53, 63, 12 and the negative electrode active material layer 55, 65, 14 of this embodiment may also be added with a conductive aid. By adding a conductive aid to the positive electrode active material layer 53, 63, 12 and the negative electrode active material layer 55, 65, 14, the conductivity can be improved. The conductive aid used in this embodiment is not particularly limited, and well-known materials can be used. The conductive aid added to the positive electrode active material layer and the negative electrode active material layer may be the same or different.
[0124] When a conductive agent is used in the positive electrode active material layers 53, 63, 12 and the negative electrode active material layers 55, 65, 14, a conductive agent with high conductivity is preferably used. For example, silver, palladium, silver-palladium alloy, gold, platinum, aluminum, copper, nickel, carbon, etc. are preferably used.
[0125] From the viewpoint of improving the electronic connection between the positive electrode active material and the positive electrode current collector layer or between the negative electrode active material and the negative electrode current collector layer, the particle size of the conductive additive is preferably 0.02 μm to 2 μm, more preferably 0.05 μm to 1 μm.
[0126] In addition, the ratio of the added conductive aid is not particularly limited as long as the positive active material or negative active material contained in the positive active material layer 53, 63, 12 and the negative active material layer 55, 65, 14 plays a role electrochemically. Preferably, the ratio of the positive active material / conductive aid or the negative active material / conductive aid is in the range of 100 / 0 to 60 / 40 by volume ratio, and more preferably in the range of 85 / 15 to 75 / 25. By setting the ratio of the conductive aid to this range, a fully solid battery with improved self-discharge characteristics, higher capacity, and higher output can be obtained, and resistance can be reduced.
[0127] (Lithium ion conductive additive)
[0128] The positive electrode active material layers 53, 63, 12 and the negative electrode active material layers 55, 65, 14 of this embodiment may also be added with a lithium ion conductive aid. This structure can improve the lithium ion conductivity. The lithium ion conductive aid used in this embodiment is not particularly limited, and well-known materials can be used. The lithium ion conductive aid added to the positive electrode active material layer and the negative electrode active material layer may be the same or different.
[0129] The lithium ion conductive aid is preferably a material with high lithium ion conductivity. It is not limited to these examples, but is preferably selected from La 0.5 Li 0.5 TiO 3 Perovskite compounds or Li 14 Zn(GeO 4 ) 4 LISICON compounds, Li 7 La 3 Zr 2 O 12 Garnet compounds, LiTi 2 (PO 4 ) 3 ,LiGe 2 (PO 4 ) 3 、LiZr 2 (PO4 ) 3 (monoclinic), LiZr 2 (PO 4 ) 3 (rhombohedral crystal), Li 1.5 Ca 0.5 Zr 1.5 (PO 4 ) 3 , Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 , Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 , Li 3 PO 4 or Li 3.5 Si 0.5 P 0.5 O 4 or Li 2.9 PO 3.3 N 0.46 , phosphorus oxide compounds such as lithium phosphate, Li 3.25 Ge 0.25 P 0.75 S 4 or Li 3 PS 4 Thio-LISICON compounds, LiPON, lithium niobate, lithium silicate, lithium borate and other oxides, Li 2 SP 2 S 5 or Li 2 OV 2 O 5 -SiO 2 At least one of the glass compounds described above.
[0130] From the perspective of ensuring good movement of lithium ions between the positive electrode active material layer 53, 63, 12 and the solid electrolyte layer 56, 66, 15 or between the negative electrode active material layer 55, 65, 14 and the solid electrolyte layer 56, 66, 15, the particle size of the lithium ion conductive aid is preferably greater than 0.02 μm and less than 2 μm, more preferably greater than 0.05 μm and less than 1 μm, and further preferably greater than 0.1 μm and less than 0.5 μm.
[0131] In addition, the ratio of the added lithium ion conductive aid is not particularly limited as long as the positive electrode active material or negative electrode active material contained in each positive electrode active material layer 53, 63, 12 or negative electrode active material layer 55, 65, 14 functions electrochemically. For example, in order to obtain an all-solid-state battery with improved self-discharge characteristics and higher capacity and high output, from the viewpoint of reducing internal resistance, the ratio of positive electrode active material / lithium ion conductive aid or negative electrode active material / lithium ion conductive aid is preferably in the range of 100 / 0 to 60 / 40 in terms of volume ratio, and more preferably in the range of 85 / 15 to 75 / 25.
[0132] (Current Collector Material)
[0133] Specific examples of collector materials constituting the positive electrode collector layers 52, 62, 12 and the negative electrode collector layers 54, 64, 13 are preferably gold (Au), platinum (Pt), platinum (Pt)-palladium (Pd), silver (Ag), silver (Ag)-palladium (Pd), aluminum (Al), copper (Cu), nickel (Ni), indium-tin oxide film (ITO), etc.
[0134] In addition, the positive electrode current collector layers 52, 62, 11, and the negative electrode current collector layers 54, 64, 13 may also contain positive electrode active materials and negative electrode active materials, respectively. The content ratio of the active materials contained in each current collector is not particularly limited as long as it functions as a current collector. For example, it is preferred that the positive electrode current collector material / positive electrode active material, or the negative electrode current collector material / negative electrode active material is in the range of 95 / 5 to 70 / 30 in volume ratio, and more preferably in the range of 90 / 10 to 75 / 25.
[0135] By having the positive electrode collector layers 52, 62, 11 and the negative electrode collector layers 54, 64, 13 contain positive electrode active materials and negative electrode active materials, respectively, the adhesion between the positive electrode collector layers 52, 62, 11 and the positive electrode active material layers, and between the negative electrode collector layers 54, 64, 13 and the negative electrode active material layers is improved, and cracks are suppressed, which is preferred.
[0136] (Sintering Aid)
[0137] The type of sintering aid added to the outer casing 51, 61, the positive electrode current collector layer 52, 62, the positive electrode active material layer 53, 63, the negative electrode current collector layer 54, 64, the negative electrode active material layer 55, 65, and the solid electrolyte layer 56, 66 constituting the all-solid-state battery 50, 60 is not particularly limited as long as it can reduce the sintering temperature. It is not limited to these examples, but for example, lithium compounds such as lithium carbonate, lithium hydroxide, and lithium phosphate or H 3 BO 3Boron compounds such as lithium and boron. The compound forms of these materials are difficult to change due to water or carbon dioxide, so they can be weighed in the air, and lithium and boron can be added simply and accurately, so they are preferred.
[0138] (Void-forming material)
[0139] The type of pore-forming material added to the outer casing 51, 61, the positive electrode active material layer 53, 63, the negative electrode active material layer 55, 65, and the solid electrolyte layer 56, 66 constituting the all-solid-state battery 50, 60 is not particularly limited as long as it can be introduced into the gap. It is not limited to these examples, but for example, it has a material that decomposes / sublimates by heat during firing, a water-soluble material, etc. The water-soluble material can be any material as long as it is soluble in water and washable. These materials can be weighed in the air and are easy to handle, so they can be accurately added, so they are preferred.
[0140] (Terminal electrode)
[0141] It is preferable to use a material with high conductivity for the terminal electrodes 57 and 67 of the all-solid batteries 50 and 60. For example, silver, gold, platinum, aluminum, copper, tin, and nickel can be used. The terminal electrodes 57 and 67 may be a single layer or a multilayer.
[0142] (Method for manufacturing all-solid-state battery)
[0143] All-solid batteries 50, 60 can be manufactured using, for example, a simultaneous firing method or a successive firing method. The simultaneous firing method is a method of stacking the materials that form each layer and firing them together to make a stack. The successive firing method is a method of making each layer in sequence, and a firing process is performed each time each layer is made. The use of the simultaneous firing method can relatively reduce the operating procedures of the all-solid batteries 50, 60. Below, the manufacturing method of the all-solid batteries 50, 60 is described by taking the case of using the simultaneous firing method as an example. As described above, the manufacturing method of the all-solid batteries 50, 60 is not limited to the simultaneous firing method, and can also be manufactured using the successive firing method.
[0144] First, the materials constituting the outer casing 51 , 61 , the positive electrode collector layer 52 , 62 , the positive electrode active material layer 53 , 63 , the solid electrolyte layer 56 , 66 , and the negative electrode collector layer 54 , 64 , and the negative electrode active material layer 55 , 65 of the all-solid-state battery 50 , 60 are made into pastes.
[0145] The method of pasting is not particularly limited. Not limited to this example, for example, the powders of each material are mixed in a solvent to obtain a paste. Here, the solvent is a general term for a liquid medium. The solvent generally contains a solvent, a dispersant, and a binder. By the above method, a paste for the outer packaging, a paste for the positive electrode collector layer, a paste for the positive electrode active material layer, a paste for the solid electrolyte layer, a paste for the negative electrode collector layer, and a paste for the negative electrode active material layer are prepared.
[0146] The composition of the paste for the positive electrode current collector layer and the paste for the negative electrode current collector layer is not particularly limited, and for example, they may contain a positive electrode active material or a negative electrode active material, a solid electrolyte, and a sintering aid in addition to the current collector material.
[0147] The composition of the paste for the positive electrode active material layer and the paste for the negative electrode active material layer is not particularly limited, but for example, they may contain a solid electrolyte, a sintering aid, a conductive aid, a lithium ion conductive aid, and a pore-forming material in addition to the positive electrode active material or the negative electrode active material.
[0148] The composition of the paste for the solid electrolyte layer is not particularly limited, but for example, it may contain a sintering aid and a pore-forming material in addition to the solid electrolyte.
[0149] The composition of the paste for the exterior portion is not particularly limited, but for example, a sintering aid and a pore-forming material may be contained in addition to the exterior portion material.
[0150] The prepared outer packaging paste and solid electrolyte layer paste are applied to a substrate such as PET (polyethylene terephthalate) in a desired order, and dried as needed to obtain an outer packaging green sheet and a solid electrolyte layer green sheet. The coating method of the paste is not particularly limited, and known methods such as screen printing, coating, transfer, and scraper can be used.
[0151] On the prepared green sheet for solid electrolyte layer or green sheet for outer packaging, the paste for positive active material layer and the paste for positive current collector layer are screen printed in a predetermined order, and the positive active material layer and the positive current collector layer are formed to prepare the positive electrode layer green sheet. In addition, depending on the situation, the printed positive active material layer and the positive current collector layer can also be changed to a screen with an unprinted pattern, and the paste for outer packaging can be printed on the unprinted part on the positive electrode layer green sheet.
[0152] The negative electrode is the same. On the solid electrolyte layer green sheet or the outer packaging green sheet, the negative electrode active material layer paste and the negative electrode collector layer paste are screen-printed in a predetermined order to form the negative electrode active material layer and the negative electrode collector layer to prepare the negative electrode layer green sheet. In addition, depending on the situation, the printed negative electrode active material layer and the negative electrode collector layer can also be changed to a screen with an unprinted pattern, and the paste for the outer packaging can be printed on the unprinted portion on the negative electrode layer green sheet.
[0153] After the outer packaging raw sheets are stacked in the desired number, the prepared positive electrode layer raw sheets and negative electrode layer raw sheets are staggered in the desired order, with the positive electrode collector layer of the positive electrode layer raw sheets only extending out of one end face, and the negative electrode collector layer of the negative electrode layer raw sheets only extending out of the other face. Then, the outer packaging raw sheets are stacked again in the desired number, thereby obtaining a pre-stacked body.
[0154] When manufacturing a parallel or series-parallel all-solid-state battery, the layers are preferably stacked in alignment and overlapped in order to stack them with high precision so that the end faces of the positive electrode active material layer and the end faces of the negative electrode active material layer do not coincide.
[0155] The produced preliminary laminate is pressure-bonded together to produce a laminate. The pressure-bonding is performed while heating, and the heating temperature is set to 40 to 90°C, for example.
[0156] The obtained laminated body is aligned and cut as necessary to produce individual laminated bodies of desired sizes. The cutting method is not limited, but it can also be performed by dicing or knife cutting.
[0157] Before the laminated body is fired into individual pieces, chamfering may be performed by dry green roll grinding or wet green roll grinding.
[0158] It can also be carried out during dry green barrel grinding with abrasives such as alumina, zirconia, resin beads, etc.
[0159] In wet green barrel grinding, a solvent is used in addition to abrasives such as alumina, zirconia, and resin beads. The solvent used in this case may be, for example, ion exchange water, purified water, or a fluorine-based solvent.
[0160] When a water-soluble pore-forming material is used, water washing can also be performed by using ion-exchanged water or purified water during wet green barrel grinding.
[0161] When dry green roll milling is performed instead of wet green roll milling, the water-soluble pore-forming material can be removed by washing with ion-exchanged water or purified water.
[0162] The monolithic laminate is heated and fired, for example, in a nitrogen atmosphere to obtain a sintered body. In the manufacture of the all-solid-state batteries 50 and 60 of the present embodiment, the firing temperature is preferably set to a range of 600 to 1200°C. This is because if it is lower than 600°C, the firing is not fully carried out. When it exceeds 1200°C, problems such as the dissolution of the collector material, the structural changes of the positive electrode active material and the negative electrode active material occur. In addition, it is more preferably set to a range of 700 to 1000°C. By setting it to a range of 700 to 1000°C, it is more suitable for promoting firing and reducing manufacturing costs. The firing time is, for example, set to 10 minutes to 3 hours.
[0163] The obtained sintered body can also be placed in a cylindrical container together with a grinding material such as alumina or resin beads, and drum-ground. Thus, the chamfering of the corners of the sintered body can be performed. As an alternative method, sandblasting can also be used for grinding. In this method, only a specific portion can be shaved off, so it is preferred.
[0164] If the terminal electrodes 57 and 67 are not formed before firing, the terminal electrodes 57 and 67 can be formed on the obtained sintered body using a known method such as sputtering, dipping, or spraying. When forming only predetermined portions, for example, the terminal electrodes 57 and 67 can be formed by masking with a tape.
[0165] There is no limitation on the method for forming the terminal electrodes 57 and 67, but specific examples of materials that can be used for the terminal electrodes 57 and 67 include gold (Au), platinum (Pt), platinum (Pt)-palladium (Pd), silver (Ag), silver (Ag)-palladium (Pd), aluminum (Al), copper (Cu), indium, indium-tin oxide film (ITO), etc.
[0166] Alternatively, the terminal electrodes 57 and 67 may be formed by mixing the above-mentioned conductive material particles with a thermosetting resin to form a thermosetting conductive paste.
[0167] The terminal electrodes 57 and 67 may be plated. The plating method and the type of coating are not particularly limited, and for example, a Ni coating may be formed by electroless Ni plating or electrolytic Ni plating, followed by Sn coating by electrolytic tin plating to form a Ni—Sn coating.
[0168] Alternatively, a coating of at least one metal such as Pt, Au, Cu, Ti, Ni, Sn, or an alloy thereof may be formed on the terminal electrodes 57 and 67 by sputtering.
[0169] The surfaces of the all-solid batteries 50 and 60 of this embodiment may be subjected to water-repellent treatment. The method of water-repellent treatment is not particularly limited, but, for example, water-repellent treatment can be performed by immersing in a solution composed of a fluororesin, a silane resin, or the like.
[0170] A glass layer may be formed on the surface of the all-solid-state battery 50 or 60 of the present embodiment. The formation method is not particularly limited, and the glass layer may be formed by applying low-melting-point glass and performing a heat treatment at a desired temperature.
[0171] The all-solid batteries 50 and 60 of this embodiment can also be housed in a highly airtight housing. The shape of the housing is not particularly limited and can be a known shape. For example, it can be a square, cylindrical, button, card, etc.
[0172] The all-solid batteries 50 and 60 of the present embodiment may also be coated with a resin. The resin that can be used is a known resin, but from the viewpoint of improving the heat resistance and moisture resistance of the coating, a fluorine-based resin, an imide-based resin, or an epoxy resin is preferably used.
[0173] The all-solid-state batteries 50 and 60 of the present embodiment may be used in combination with other lithium-ion secondary batteries, solar power generation units, wind power generation units, geothermal power generation units, piezoelectric elements, thermoelectric elements, and the like.
[0174] The embodiments of the present invention are described in detail with reference to the accompanying drawings, but the structures of the embodiments and their combinations are examples, and addition, omission, substitution, and other changes of the structures can be made within the scope of the purpose of the present invention. It is also possible to appropriately combine and implement a plurality of embodiments within the scope of achieving the effect.
[0175] Example
[0176] Hereinafter, the present invention will be described in detail using Examples, but the present invention is not limited to these Examples. In addition, parts are parts by weight unless otherwise specified.
[0177] (Example 1)
[0178] (Preparation of positive electrode active material)
[0179] As the positive electrode active material, Li prepared by the following method was used. 3 V 2 (PO 4 ) 3 . 2 CO 3 、V 2 O 5 NH 4 H 2 PO 4As the starting materials, they were weighed in a molar ratio of 3:2:6, wet mixed for 16 hours using a ball mill with water as solvent, and then dehydrated and dried. The obtained powder was calcined at 850°C in a nitrogen-hydrogen mixed gas for 2 hours. The calcined product was coarsely crushed, wet crushed for 24 hours using a ball mill with ethanol as solvent, and then dried to obtain a positive electrode active material powder. The average particle size of the powder was 0.3μm. The produced powder is Li 3 V 2 (PO 4 ) 3 The confirmation was performed using an X-ray diffraction apparatus.
[0180] (Preparation of positive electrode active material paste)
[0181] In the case of the positive electrode active material paste, the prepared Li 3 V 2 (PO 4 ) 3 To 100 parts of the active material powder, 15 parts of ethyl cellulose as a binder and 65 parts of dihydroterpineol as a solvent were added, and the mixture was kneaded and dispersed using a mixer to prepare a positive electrode active material paste.
[0182] (Preparation of negative electrode active material)
[0183] As the negative electrode active material, Li prepared by the following method was used. 4 Ti 5 O 12 . 2 CO 3 、TiO 2 As the starting materials, they were weighed in a molar ratio of 2:5, wet mixed for 16 hours using a ball mill with water as solvent, and then dehydrated and dried. The obtained powder was calcined at 950°C in atmospheric gas for 4 hours. The calcined product was coarsely crushed, wet crushed for 16 hours using a ball mill with ethanol as solvent, and then dehydrated and dried to obtain a negative electrode active material powder. The average particle size of the powder was 0.4μm. An X-ray diffraction device was used to confirm that the produced powder was Li 4 Ti 5 O 12 .
[0184] (Preparation of Negative Electrode Active Material Paste)
[0185] For the negative electrode active material paste, the prepared Li 4 Ti 5 O 12The powder and the copper powder were mixed at a volume ratio of 70 / 30, and then 15 parts of ethyl cellulose as a binder and 65 parts of dihydroterpineol as a solvent were added and kneaded and dispersed using a mixer to prepare a negative electrode active material paste.
[0186] (Solid Electrolyte)
[0187] As the solid electrolyte, LiTi prepared by the following method was used. 2 (PO 4 ) 3 . 2 CO 3 、TiO 2 NH 4 H 2 PO 4 As the starting materials, they were weighed in a molar ratio of 1:2:6, wet mixed for 16 hours using a ball mill with water as solvent, and then dehydrated and dried. The obtained powder was calcined in air at 800°C for 2 hours. The calcined product was coarsely crushed, wet crushed for 16 hours using a ball mill with ethanol as solvent, and then dehydrated and dried to obtain a solid electrolyte powder. The average particle size of the powder was 0.4μm. An X-ray diffraction device was used to confirm that the produced powder was LiTi 2 (PO 4 ) 3 .
[0188] (Solid electrolyte layer sheet)
[0189] As for the solid electrolyte layer sheet, the LiTi 2 (PO 4 ) 3 To 100 parts of the powder, 100 parts of ethanol and 200 parts of toluene as solvents were added by a ball mill and wet mixed. Then, 16 parts of a polyvinyl butyral-based binder and 4.8 parts of butyl benzyl phthalate were further added and mixed to prepare a solid electrolyte slurry. The solid electrolyte slurry was formed into a sheet using a PET film as a substrate by a doctor blade method to obtain a solid electrolyte layer sheet with a thickness of 15 μm.
[0190] (Exterior materials)
[0191] As the outer material, LiZr prepared by the following method was used. 2 (PO 4 ) 3 Monoclinic powder. 2 CO 3 、ZrO 2 NH 4 H2 PO 4 As the initial material, they were weighed in a molar ratio of 1:2:6, wet mixed for 16 hours using a ball mill with water as solvent, and then dehydrated and dried. The obtained powder was calcined in air at 900°C for 3 hours. The calcined product was coarsely crushed, wet crushed for 16 hours using a ball mill with ethanol as solvent, and then dehydrated and dried to obtain a powder of the outer material. The average particle size of the powder was 0.5μm. An X-ray diffraction device was used to confirm that the produced powder was LiZr 2 (PO 4 ) 3 Monoclinic.
[0192] (Exterior decoration sheet)
[0193] As for the exterior sheet, by adding the LiZr 2 (PO 4 ) 3 To 100 parts of the monoclinic powder, 100 parts of ethanol and 200 parts of toluene as solvents were added by a ball mill and wet mixed. Then, 16 parts of a polyvinyl butyral adhesive and 4.8 parts of butyl benzyl phthalate were further added and mixed to prepare an exterior slurry. The exterior slurry was formed into a sheet using a PET film as a substrate by a doctor blade method to obtain an exterior sheet with a thickness of 15 μm.
[0194] (Exterior coating paste)
[0195] For the exterior paste, the LiZr 2 (PO 4 ) 3 To 100 parts of the monoclinic powder, 15 parts of ethyl cellulose as a binder and 65 parts of dihydroterpineol as a solvent were added, and the mixture was kneaded and dispersed using a mixer to prepare a positive electrode active material paste.
[0196] (Preparation of positive electrode collector paste)
[0197] As a positive electrode current collector paste, copper powder and Li 3 V 2 (PO 4 ) 3 The powders were mixed at a volume ratio of 80 / 20, and then 10 parts of ethyl cellulose as a binder and 50 parts of dihydroterpineol as a solvent were added and kneaded and dispersed using three rolls to prepare a positive electrode current collector paste.
[0198] (Preparation of Negative Electrode Collector Paste)
[0199] As a negative electrode current collector paste, copper powder and Li 4 Ti 5O 12 The powders were mixed at a volume ratio of 80 / 20, and then 10 parts of ethyl cellulose as a binder and 50 parts of dihydroterpineol as a solvent were added, followed by kneading and dispersion using three rolls to prepare a negative electrode current collector paste.
[0200] Using these pastes, all-solid batteries were produced as follows.
[0201] (Fabrication of Positive Electrode Active Material Unit)
[0202] On the above-mentioned solid electrolyte layer sheet, the positive electrode active material paste is printed with a thickness of 5μm by screen printing. Then, after the printed positive electrode active material paste is dried at 80-100°C for 5-10 minutes, the positive electrode collector paste is printed thereon with a thickness of 5μm by screen printing. Next, the printed positive electrode collector paste is dried at 80-100°C for 5-10 minutes, and further thereon, the positive electrode active material paste is printed again with a thickness of 5μm by screen printing. The printed positive electrode active material paste is dried at 80-100°C for 5-10 minutes. Next, the screen is changed, and the outer packaging paste is printed with a thickness of 15μm in the part where the positive electrode active material paste and the positive electrode collector paste are not printed, and dried at 80-100°C for 5-10 minutes, and then the PET film is peeled off. In this way, a positive electrode active material unit is obtained in which the positive electrode active material paste, the positive electrode current collector paste, the positive electrode active material paste, and the exterior portion paste are printed and dried on the solid electrolyte layer sheet.
[0203] (Fabrication of Negative Electrode Active Material Unit)
[0204] On the above-mentioned solid electrolyte layer sheet, the negative electrode active material paste is printed with a thickness of 10 μm by screen printing. Then, after the printed negative electrode active material paste is dried at 80-100°C for 5-10 minutes, the negative electrode collector paste is printed thereon with a thickness of 5 μm by screen printing. Next, the printed negative electrode collector paste is dried at 80-100°C for 5-10 minutes, and the negative electrode active material paste is printed again thereon with a thickness of 10 μm by screen printing. The printed negative electrode active material paste is dried at 80-100°C for 5-10 minutes. Next, the screen is changed, and the outer packaging paste is printed with a thickness of 25 μm in the part where the negative electrode active material paste and the negative electrode collector paste are not printed, and dried at 80-100°C for 5-10 minutes, and then the PET film is peeled off. In this way, a negative electrode active material unit is obtained in which the negative electrode active material paste, the negative electrode current collector paste, the negative electrode active material paste, and the exterior portion paste are printed and dried on the solid electrolyte layer sheet.
[0205] (Production of Laminated Body)
[0206] Overlap 10 sheets of the outer packaging, and for 13 sheets of positive active material units and 13 sheets of negative active material units, overlap and stack the paste printed surface downward in the order of positive active material units and negative active material units. At this time, the units are overlapped in a staggered manner in which the positive collector paste layer of the positive active material unit only extends from one end face, and the negative collector paste layer of the negative active material unit extends from the other side. In addition, overlap 10 sheets of the outer packaging. Then, it is formed at a temperature of 80°C and a pressure of 1000kgf / cm2 (98MPa), and then cut to make a stacked block. Then, the stacked blocks are fired simultaneously to obtain a sintered body. During the simultaneous firing, the temperature is raised in nitrogen at a heating rate of 200°C / hour to a firing temperature of 900°C, maintained at this temperature for 0.5 hours, and naturally cooled after firing. The external dimensions of the battery after simultaneous firing are 3.2mm×2.5mm×1.0mm.
[0207] (Terminal electrode formation)
[0208] Then, an InGa electrode paste was applied to each of the positive electrode collector layer and the negative electrode collector layer of the obtained sintered body and dried, and terminal electrodes were attached to the positive electrode collector layer and the negative electrode collector layer to produce an all-solid-state battery.
[0209] (evaluate)
[0210] The chemical composition and crystal structure of the produced solid electrolyte and exterior material were measured by the following methods.
[0211] (Chemical Composition)
[0212] The solid electrolyte and the outer casing material were measured by ICP-AES to analyze the composition of the solid electrolyte and the outer casing material.
[0213] (Crystal Structure)
[0214] The X-ray diffraction patterns of the solid electrolyte and the exterior material are measured by powder X-ray diffraction, and the crystal structures of the solid electrolyte and the exterior material are identified using the obtained X-ray diffraction patterns.
[0215] (Lithium ion conductivity)
[0216] The ionic conductivity of the solid electrolyte layer and the ionic conductivity of the outer casing were measured by the following method. 0.5 g of the solid electrolyte or outer casing material was weighed and placed in a metal mold with a diameter of 12 mm. 2After cold pressing under pressure, it is sintered at 900°C for 2 hours to obtain a solid electrolyte layer sintered body or an outer casing sintered body. After shielding the periphery of the obtained solid electrolyte layer sintered body or the outer casing sintered body to prevent short circuit, gold is sputtered on both sides to form gold electrodes. Next, the shielding is removed. The lithium ion conductivity is measured using an impedance measuring device (manufactured by Solartron, model SI1260) under the conditions of an amplitude of 50mV and a frequency of 0.02Hz to 1MHz. The ion conductivity is calculated based on the measured value, the thickness and area of the solid electrolyte sintered body or the outer casing sintered body. The ion conductivity of the solid electrolyte layer, the ion conductivity of the outer casing, and the ion conductivity ratio Y are shown in Table 1.
[0217] The ion conductivity ratio Y in this example is a value calculated by dividing the obtained ion conductivity of the exterior portion by the ion conductivity of the solid electrolyte layer.
[0218] (Example 2)
[0219] In addition to using LiGe prepared by the following method as the solid electrolyte 2 (PO 4 ) 3 A solid-state battery was produced in the same manner as in Example 1 except for the above.
[0220] Li 2 CO 3 ,GeO 2 NH 4 H 2 PO 4 As the starting materials, they were weighed in a molar ratio of 1:2:6, wet mixed for 16 hours using a ball mill with water as solvent, and then dehydrated and dried. The obtained powder was calcined in air at 900°C for 3 hours. The calcined product was coarsely crushed, wet crushed for 16 hours using a ball mill with ethanol as solvent, and then dehydrated and dried to obtain a solid electrolyte powder. The average particle size of the powder was 0.5μm. An X-ray diffraction device was used to confirm that the produced powder was LiGe 2 (PO 4 ) 3 Table 1 shows the ion conductivity and ion conductivity ratio Y of the solid electrolyte layer and the exterior portion.
[0221] (Example 3)
[0222] In addition to using LiZr prepared by the following method as the solid electrolyte 2 (PO 4 ) 3 An all-solid-state battery was produced in the same manner as in Example 1 except for the rhombohedral crystal.
[0223] LiZr was produced in the following order 2 (PO 4 ) 3 First, weigh LiOH·H 2 O、ZrO(NO 3 ) 2 NH 4 (H 2 PO 4 ) and dissolve each in water. The solutions were mixed, the pH was adjusted, and then heated to 80°C, and then gradually cooled. The crystal phase of the single crystal confirmed by X-ray diffraction was rhombohedral crystal, and the particle size (D50) was 0.6μm. The ionic conductivity of the solid electrolyte layer and the outer packaging and the ionic conductivity ratio Y are shown in Table 1.
[0224] (Example 4)
[0225] In addition to using Li prepared by the following method as the solid electrolyte 1.5 Ca 0.5 Zr 1.5 (PO 4 ) 3 An all-solid-state battery was produced in the same manner as in Example 1 except for the rhombohedral crystal.
[0226] Li 2 CO 3 、CaCO 3 、ZrO 2 NH 4 H 2 PO 4 As the starting materials, they were weighed in a molar ratio of 1.5:1:3:6, wet mixed for 16 hours using a ball mill with water as solvent, and then dehydrated and dried. The obtained powder was calcined in air at 1200°C for 2 hours. The calcined product was coarsely crushed, wet crushed for 16 hours using a ball mill with ethanol as solvent, and then dehydrated and dried to obtain a solid electrolyte powder. The average particle size of the powder was 0.5μm. An X-ray diffraction device was used to confirm that the produced powder was Li 1.5 Ca 0.5 Zr 1.5 (PO 4 ) 3 Table 1 shows the ion conductivity and ion conductivity ratio Y of the solid electrolyte layer and the exterior portion.
[0227] (Example 5)
[0228] In addition to using Li prepared by the following method as the solid electrolyte 1.3 Al 0.3 Ti1.7 (PO 4 ) 3 A solid-state battery was produced in the same manner as in Example 1 except for the above.
[0229] Li 2 CO 3 、Al 2 O 3 、TiO 2 NH 4 H 2 PO 4 As the starting materials, they were weighed in a molar ratio of 0.85:0.15:1.7:3, wet mixed for 16 hours using a ball mill with water as solvent, and then dehydrated and dried. The obtained powder was calcined in air at 800°C for 2 hours. The calcined product was coarsely crushed, wet crushed for 16 hours using a ball mill with ethanol as solvent, and then dehydrated and dried to obtain a solid electrolyte powder. The average particle size of the powder was 0.5μm. An X-ray diffraction device was used to confirm that the produced powder was Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 Table 1 shows the ion conductivity and ion conductivity ratio Y of the solid electrolyte layer and the exterior portion.
[0230] (Example 6)
[0231] In addition to using Li prepared by the following method as the solid electrolyte 1.3 Al 0.3 Ge 1.7 (PO 4 ) 3 A solid-state battery was produced in the same manner as in Example 1 except for the above.
[0232] Li 2 CO 3 、Al 2 O 3 ,GeO 2 NH 4 H 2 PO 4 As the starting materials, they were weighed in a molar ratio of 0.85:0.15:1.7:3, wet mixed for 16 hours using a ball mill with water as solvent, and then dehydrated and dried. The obtained powder was calcined in air at 900°C for 2 hours. The calcined product was coarsely crushed, wet crushed for 16 hours using a ball mill with ethanol as solvent, and then dehydrated and dried to obtain a solid electrolyte powder. The average particle size of the powder was 0.5μm. An X-ray diffraction device was used to confirm that the produced powder was Li 1.3Al 0.3 Ge 1.7 (PO 4 ) 3 Table 1 shows the ion conductivity and ion conductivity ratio Y of the solid electrolyte layer and the exterior portion.
[0233] (Example 7)
[0234] In addition to using Li prepared by the following method as the solid electrolyte 3.5 Si 0.5 P 0.5 O 4 A solid-state battery was produced in the same manner as in Example 1 except for the above.
[0235] Li 2 CO 3 、SiO 2 , Li 3 PO 4 As the starting materials, they were weighed in a molar ratio of 2:1:1, wet mixed for 16 hours using a ball mill with water as solvent, and then dehydrated and dried. The obtained powder was calcined in air at 950°C for 2 hours. The calcined product was coarsely crushed, wet crushed for 16 hours using a ball mill with ethanol as solvent, and then dehydrated and dried to obtain a solid electrolyte powder. The average particle size of the powder was 0.6μm. An X-ray diffraction device was used to confirm that the produced powder was Li 3.5 Si 0.5 P 0.5 O 4 Table 1 shows the ion conductivity and ion conductivity ratio Y of the solid electrolyte layer and the exterior portion.
[0236] (Example 8)
[0237] In addition to using Li prepared by the following method as the solid electrolyte 7 La 3 Zr 2 O 12 A solid-state battery was produced in the same manner as in Example 1 except for the above.
[0238] Li 2 CO 3 ,La 2 O 3 、ZrO 2As the starting materials, they were weighed in a molar ratio of 7:3:4, wet mixed for 16 hours using a ball mill with water as solvent, and then dehydrated and dried. The obtained powder was calcined in air at 950°C for 5 hours. The calcined product was coarsely crushed, wet crushed for 16 hours using a ball mill with ethanol as solvent, and then dehydrated and dried to obtain a solid electrolyte powder. The average particle size of the powder was 0.5μm. An X-ray diffraction device was used to confirm that the produced powder was Li 7 La 3 Zr 2 O 12 Table 1 shows the ion conductivity and ion conductivity ratio Y of the solid electrolyte layer and the exterior portion.
[0239] (Examples 9-10)
[0240] In addition to using LiZr produced by the following method as the outer material 2 (PO 4 ) 3 Except for the rhombohedral crystal, an all-solid-state battery was produced in the same manner as in Example 3 and Example 5.
[0241] LiZr was produced in the following order 2 (PO 4 ) 3 First, LiOH·H 2 O、ZrO(NO 3 ) 2 NH 4 (H 2 PO 4 ) were weighed in a stoichiometric ratio and dissolved in water. The solutions were mixed, heated to 80°C after adjusting the pH, and then gradually cooled. The crystal phase of the single crystal confirmed by X-ray diffraction was rhombohedral crystal with a particle size (D50) of 0.6 μm. The ionic conductivity of the solid electrolyte layer and the outer packaging and the ionic conductivity ratio Y are shown in Table 1.
[0242] (Example 11)
[0243] In addition to using Li produced by the following method as the exterior material 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 A solid-state battery was produced in the same manner as in Example 5 except for the above.
[0244] Li 2 CO 3 、Al 2 O 3 、TiO2 NH 4 H 2 PO 4 As the starting materials, they were weighed in a molar ratio of 0.85:0.15:1.7:3, wet mixed for 16 hours using a ball mill with water as solvent, and then dehydrated and dried. The obtained powder was calcined in air at 800°C for 2 hours. The calcined product was coarsely crushed, wet crushed for 16 hours using a ball mill with ethanol as solvent, and then dehydrated and dried to obtain a solid electrolyte powder. The average particle size of the powder was 0.5μm. An X-ray diffraction device was used to confirm that the produced powder was Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 Table 1 shows the ion conductivity and ion conductivity ratio Y of the solid electrolyte layer and the exterior portion.
[0245] (Example 12)
[0246] In addition to using LiZr produced by the following method as the outer material 2 (PO 4 ) 3 An all-solid-state battery was produced in the same manner as in Example 6 except for the rhombohedral crystal.
[0247] LiZr is made in the following order 2 (PO 4 ) 3 First, LiOH·H 2 O、ZrO(NO 3 ) 2 NH 4 (H 2 PO 4 ) were weighed in a stoichiometric ratio and dissolved in water. The solutions were mixed, heated to 80°C after adjusting the pH, and then gradually cooled. The crystal phase of the single crystal confirmed by X-ray diffraction was rhombohedral crystal with a particle size (D50) of 0.6 μm. The ionic conductivity of the solid electrolyte layer and the outer packaging and the ionic conductivity ratio Y are shown in Table 1.
[0248] (Example 13)
[0249] In addition to using Li produced by the following method as the exterior material 1.3 Al 0.3 Ge 1.7 (PO 4 ) 3 A fully solid-state battery was produced in the same manner as in Example 6 except for the above.
[0250] Li 2 CO 3 、Al 2 O 3 ,GeO 2 NH 4 H 2 PO 4 As the starting materials, they were weighed in a molar ratio of 0.85:0.15:1.7:3, wet mixed for 16 hours using a ball mill with water as solvent, and then dehydrated and dried. The obtained powder was calcined in air at 900°C for 2 hours. The calcined product was coarsely crushed, wet crushed for 16 hours using a ball mill with ethanol as solvent, and then dehydrated and dried to obtain a solid electrolyte powder. The average particle size of the powder was 0.5μm. An X-ray diffraction device was used to confirm that the produced powder was Li 1.3 Al 0.3 Ge 1.7 (PO 4 ) 3 Table 1 shows the ion conductivity and ion conductivity ratio Y of the solid electrolyte layer and the exterior portion.
[0251] (Example 14)
[0252] In addition to using LiZr produced by the following method as the outer material 2 (PO 4 ) 3 An all-solid-state battery was produced in the same manner as in Example 7 except for the rhombohedral crystal.
[0253] LiZr was produced in the following order 2 (PO 4 ) 3 First, LiOH·H 2 O、ZrO(NO 3 ) 2 NH 4 (H 2 PO 4 ) were weighed in a stoichiometric ratio and dissolved in water. The solutions were mixed, heated to 80°C after adjusting the pH, and then gradually cooled. The crystal phase of the single crystal confirmed by X-ray diffraction was rhombohedral crystal with a particle size (D50) of 0.6 μm. The ionic conductivity of the solid electrolyte layer and the outer packaging and the ionic conductivity ratio Y are shown in Table 1.
[0254] (Example 15)
[0255] In addition to the exterior material, Li was used, which was produced by the following method. 3.5 Si 0.5 P0.5 O 4 A fully solid-state battery was produced in the same manner as in Example 7 except for the above.
[0256] Li 2 CO 3 、SiO 2 , Li 3 PO 4 As the starting materials, they were weighed in a molar ratio of 2:1:1, wet mixed for 16 hours using a ball mill with water as solvent, and then dehydrated and dried. The obtained powder was calcined in air at 950°C for 2 hours. The calcined product was coarsely crushed, wet crushed for 16 hours using a ball mill with ethanol as solvent, and then dehydrated and dried to obtain a solid electrolyte powder. The average particle size of the powder was 0.6μm. An X-ray diffraction device was used to confirm that the produced powder was Li 3.5 Si 0.5 P 0.5 O 4 Table 1 shows the ion conductivity and ion conductivity ratio Y of the solid electrolyte layer and the exterior portion.
[0257] (Example 16)
[0258] In addition to using LiZr produced by the following method as the outer material 2 (PO 4 ) 3 An all-solid-state battery was produced in the same manner as in Example 4 except for the rhombohedral crystal.
[0259] LiZr is made in the following order 2 (PO 4 ) 3 First, LiOH·H 2 O、ZrO(NO 3 ) 2 NH 4 (H 2 PO 4 ) were weighed in a stoichiometric ratio and dissolved in water. The solutions were mixed, heated to 80°C after adjusting the pH, and then gradually cooled. The crystal phase of the single crystal confirmed by X-ray diffraction was rhombohedral crystal with a particle size (D50) of 0.6 μm. The ionic conductivity of the solid electrolyte layer and the outer packaging and the ionic conductivity ratio Y are shown in Table 1.
[0260] (Example 17)
[0261] A solid-state battery was produced in the same manner as in Example 1 except that the ion conductivity and self-discharge characteristics were evaluated in a thermostatic chamber at 60° C. Table 1 shows the ion conductivity and ion conductivity ratio Y of the solid electrolyte layer and the exterior portion.
[0262] (Example 18)
[0263] In addition to using ZrO as the exterior material 2 A solid-state battery was produced in the same manner as in Example 3 except for the above. Table 1 shows the ion conductivity and ion conductivity ratio Y of the solid electrolyte layer and the exterior portion.
[0264] (Example 19)
[0265] In addition to using Al as the exterior material 2 O 3 A solid-state battery was produced in the same manner as in Example 3 except for the above. Table 1 shows the ion conductivity and ion conductivity ratio Y of the solid electrolyte layer and the exterior portion.
[0266] (Example 20)
[0267] In addition to using LiZr 2 (PO 4 ) 3 Monoclinic crystal is used as solid electrolyte, and LiZr is used 2 (PO 4 ) 3 A full solid-state battery was produced in the same manner as in Example 1 except that rhombohedral crystals were used as the outer casing material. Table 1 shows the ion conductivity and ion conductivity ratio Y of the solid electrolyte layer and the outer casing.
[0268] (Example 21)
[0269] In addition to using LiTi 2 (PO 4 ) 3 As a solid electrolyte, Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 A full solid-state battery was produced in the same manner as in Example 1 except for the material of the exterior portion. Table 1 shows the ion conductivity and ion conductivity ratio Y of the solid electrolyte layer and the exterior portion.
[0270] (Example 22)
[0271] In addition to using LiGe 2 (PO 4 ) 3 As a solid electrolyte, Li1.3 Al 0.3 Ge 1.7 (PO 4 ) 3 Except for the material of the exterior part, a full solid battery was produced in the same manner as in Example 1. Table 1 shows the ion conductivity and ion conductivity ratio Y of the solid electrolyte layer and the exterior part.
[0272] (Example 23)
[0273] In addition to using LiGe 2 (PO 4 ) 3 As a solid electrolyte, LiZr is used 2 (PO 4 ) 3 A full solid-state battery was produced in the same manner as in Example 1 except that rhombohedral crystals were used as the outer casing material. Table 1 shows the ion conductivities and ion conductivity ratios Y of the solid electrolyte layer and the outer casing.
[0274] (Example 24)
[0275] In addition to using LiZr 2 (PO 4 ) 3 Monoclinic crystal is used as solid electrolyte, and Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 A solid-state battery was produced in the same manner as in Example 1 except that the ion conductivity and self-discharge characteristics were evaluated in a thermostatic chamber at 60° C. The ion conductivities and ion conductivity ratios Y of the solid electrolyte layer and the outer casing are shown in Table 1.
[0276] (Self-discharge characteristics evaluation)
[0277] The terminal electrodes of the all-solid batteries produced in Examples 1 to 24 were attached to a jig of a type that was fixed with a spring pin.
[0278] First, the all-solid-state battery was charged at a constant current of 1 μA to a cut-off voltage of 2.8V. Then, the fully charged all-solid-state battery was removed and stored in a thermostatic chamber at 25°C for one month. After one month, it was installed in a fixture and discharged at a constant current of 1 μA to a cut-off voltage of 1.8V to obtain the self-discharge rate. In addition, in the embodiments, unless the evaluation temperature is specified, the evaluation is performed in a thermostatic chamber at 25°C. In addition, when the temperature is specified in the embodiments, the evaluation is performed in a thermostatic chamber at the specified temperature. Here, the self-discharge rate is calculated as {1-(discharge capacity after storage for one month / full charge capacity)}×100.
[0279] [Table 1]
[0280]
[0281] In the all-solid batteries prepared in Examples 1 to 24, the self-discharge rate was small. It was possible to obtain an all-solid battery with high self-discharge characteristics. In particular, the all-solid batteries of Examples 1 to 19 were -6 ≤Y≤1, the self-discharge rate can be reduced compared with Examples 20 to 24.
[0282] (Example 25)
[0283] In Example 25, a fully solid-state battery was produced in the same manner as in Example 1, except that the outer packaging sheet and the outer packaging paste were prepared by adding 0.5 vol% of sucrose by volume, and the outer packaging sheets and the outer packaging paste were stacked and cut into blocks, and then washed with ion exchange water for 5 minutes. The porosity P and the self-discharge rate of the outer packaging are shown in Table 2.
[0284] (Example 26)
[0285] In Example 26, a fully solid-state battery was produced in the same manner as in Example 2, except that the outer packaging sheet and the outer packaging paste were prepared by adding 1.2 vol% of sucrose by volume, and the stacking and cutting were performed to form a stacked block, and then the stacking block was washed with ion exchange water for 5 minutes. The porosity P and the self-discharge rate of the outer packaging are shown in Table 2.
[0286] (Example 27)
[0287] In Example 27, a fully solid-state battery was produced in the same manner as in Example 3, except that the outer packaging sheet and the outer packaging paste were prepared by adding 0.3 vol% of sucrose by volume, and the stacking and cutting were performed to form a stacked block, and then the stacking block was washed with ion exchange water for 5 minutes. The porosity P and the self-discharge rate of the outer packaging are shown in Table 2.
[0288] (Example 28)
[0289] In Example 28, a fully solid-state battery was produced in the same manner as in Example 4, except that the outer packaging sheet and the outer packaging paste to which 0.4 vol% of sucrose was added were prepared, and the stacking blocks were stacked and cut, and then washed with ion exchange water for 5 minutes. The porosity P and the self-discharge rate of the outer packaging are shown in Table 2.
[0290] (Example 29)
[0291] In Example 29, a fully solid-state battery was produced in the same manner as in Example 5, except that the outer packaging sheet and the outer packaging paste were prepared by adding 2.3 vol% of sucrose by volume, and the stacking and cutting were performed to form a stacked block, and then the stacking block was washed with ion exchange water for 5 minutes. The porosity P and the self-discharge rate of the outer packaging are shown in Table 2.
[0292] (Example 30)
[0293] In Example 30, a fully solid-state battery was produced in the same manner as in Example 6, except that the outer packaging sheet and the outer packaging paste were prepared by adding 2.1 vol% of sucrose by volume, and the stacking and cutting were performed to form a stacked block, and then the stacking block was washed with ion exchange water for 5 minutes. The porosity P and the self-discharge rate of the outer packaging are shown in Table 2.
[0294] (Example 31)
[0295] In Example 31, a fully solid-state battery was produced in the same manner as in Example 7, except that the outer packaging sheet and the outer packaging paste were prepared by adding 2 vol% of sucrose by volume, and the stacking and cutting were performed to form a stacked block, and then the stacking block was washed with ion exchange water for 5 minutes. The porosity P and the self-discharge rate of the outer packaging are shown in Table 2.
[0296] (Example 32)
[0297] In Example 32, a fully solid-state battery was produced in the same manner as in Example 8, except that the outer casing sheet and the outer casing paste were prepared by adding 3 vol% of sucrose by volume, and the stacking and cutting were performed to form a stacked block, and then the stacking block was washed with ion exchange water for 5 minutes. The porosity P and the self-discharge rate of the outer casing are shown in Table 2.
[0298] (Example 33)
[0299] In Example 33, a fully solid-state battery was produced in the same manner as in Example 9, except that the outer packaging sheet and the outer packaging paste were prepared by adding 0.8 vol% of sucrose by volume, and the outer packaging sheets and the outer packaging paste were stacked and cut to form a stacked block, and then washed with ion exchange water for 5 minutes. The porosity P and the self-discharge rate of the outer packaging are shown in Table 2.
[0300] (Example 34)
[0301] In Example 34, a fully solid-state battery was produced in the same manner as in Example 10, except that the outer packaging sheet and the outer packaging paste were prepared by adding 0.3 vol% of sucrose by volume, and the outer packaging sheets and the outer packaging paste were stacked and cut into blocks, and then washed with ion exchange water for 5 minutes. The porosity P and the self-discharge rate of the outer packaging are shown in Table 2.
[0302] (Example 35)
[0303] In Example 35, a fully solid-state battery was produced in the same manner as in Example 12, except that the outer packaging sheet and the outer packaging paste were prepared by adding 2.5 vol% of sucrose by volume, and the stacking and cutting were performed to form a stacked block, and then the stacking block was washed with ion exchange water for 5 minutes. The porosity P and the self-discharge rate of the outer packaging are shown in Table 2.
[0304] (Example 36)
[0305] In Example 36, a fully solid-state battery was produced in the same manner as in Example 14, except that the outer packaging sheet and the outer packaging paste were prepared by adding 1.2 vol% of sucrose by volume, and the stacking and cutting were performed to form a stacked block, and then the stacking block was washed with ion exchange water for 5 minutes. The porosity P and the self-discharge rate of the outer packaging are shown in Table 2.
[0306] (Example 37)
[0307] In Example 37, a fully solid-state battery was produced in the same manner as in Example 16, except that the outer packaging sheet and the outer packaging paste were prepared by adding 1.5 vol% of sucrose by volume, and the stacking and cutting were performed to form a stacked block, and then the stacking block was washed with ion exchange water for 5 minutes. The porosity P and the self-discharge rate of the outer packaging are shown in Table 2.
[0308] (Example 38)
[0309] In Example 38, in addition to using Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 As the outer casing material, an outer casing sheet and an outer casing paste to which 0.3 vol% of sucrose was added were prepared, and the sheets and pastes were stacked and cut to form a stacked block, and then washed with ion exchange water for 5 minutes. The other procedures were the same as in Example 3 to produce an all-solid-state battery. The porosity P and self-discharge rate of the outer casing are shown in Table 2.
[0310] (Example 39)
[0311] In Example 39, a fully solid-state battery was produced in the same manner as in Example 11, except that the outer packaging sheet and the outer packaging paste were prepared by adding 0.4 vol% of sucrose by volume, and the stacking and cutting were performed to form a stacked block, and then the stacking block was washed with ion exchange water for 5 minutes. The porosity P and the self-discharge rate of the outer packaging are shown in Table 2.
[0312] (Example 40)
[0313] In Example 40, in addition to using Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 As the outer casing material, an outer casing sheet and an outer casing paste to which 1 vol% sucrose was added were prepared, and the sheets and pastes were stacked and cut to form a stacked block, and then washed with ion exchange water for 5 minutes. The other procedures were the same as in Example 6 to produce an all-solid-state battery. The porosity P and self-discharge rate of the outer casing are shown in Table 2.
[0314] (Example 41)
[0315] In Example 41, in addition to using Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 As the outer casing material, an outer casing sheet and an outer casing paste to which sucrose was added at a volume ratio of 1.4 vol% were prepared, and the sheets and pastes were stacked and cut to form a stacked block, and then washed with ion exchange water for 5 minutes. The other procedures were the same as in Example 7 to produce an all-solid-state battery. The porosity P and self-discharge rate of the outer casing are shown in Table 2.
[0316] (Example 42)
[0317] In Example 42, in addition to using Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 As the outer casing material, an outer casing sheet and an outer casing paste to which sucrose was added at a volume ratio of 2.4 vol% were prepared, and the sheets and the outer casing pastes were stacked and cut to form a stacked block, and then washed with ion exchange water for 5 minutes. The other procedures were the same as in Example 4 to produce an all-solid-state battery. The porosity P and the self-discharge rate of the outer casing are shown in Table 2.
[0318] (Example 43)
[0319] In Example 43, a fully solid-state battery was produced in the same manner as in Example 18, except that the outer packaging sheet and the outer packaging paste were prepared by adding 1.8 vol% of sucrose by volume, and the stacking was performed by stacking and cutting, and then washed with ion exchange water for 5 minutes. The porosity P and the self-discharge rate of the outer packaging are shown in Table 2.
[0320] (Example 44)
[0321] In Example 44, an all-solid-state battery was produced in the same manner as in Example 19, except that the outer packaging sheet and the outer packaging paste were prepared by adding 2 vol% of sucrose by volume, and the stacking and cutting were performed to form a stacked block, and then the stacking block was washed with ion exchange water for 5 minutes. The porosity P and the self-discharge rate of the outer packaging are shown in Table 2.
[0322] (Example 45)
[0323] In Example 45, a fully solid-state battery was produced in the same manner as in Example 13, except that the outer packaging sheet and the outer packaging paste were prepared by adding 0.3 vol% of sucrose by volume, and the stacking and cutting were performed to form a stacked block, and then the stacking block was washed with ion exchange water for 5 minutes. The porosity P and the self-discharge rate of the outer packaging are shown in Table 2.
[0324] (Example 46)
[0325] In Example 46, an all-solid-state battery was produced in the same manner as in Example 15, except that the outer casing sheet and outer casing paste to which 1 vol% sucrose was added were prepared, stacked, cut and stacked into blocks, and then washed with ion exchange water for 5 minutes. The porosity P and self-discharge rate of the outer casing are shown in Table 2.
[0326] (Example 47)
[0327] In Example 47, a fully solid-state battery was produced in the same manner as in Example 20, except that the outer packaging sheet and the outer packaging paste were prepared by adding 3.3 vol% of sucrose by volume, and the stacking and cutting were performed to form a stacked block, and then the stacking block was washed with ion exchange water for 5 minutes. The porosity P and the self-discharge rate of the outer packaging are shown in Table 2.
[0328] (Example 48)
[0329] In Example 48, a fully solid-state battery was produced in the same manner as in Example 21, except that the outer packaging sheet and the outer packaging paste were prepared by adding 4 vol% of sucrose by volume, and the stacking and cutting were performed to form a stacked block, and then the stacking block was washed with ion exchange water for 5 minutes. The porosity P and the self-discharge rate of the outer packaging are shown in Table 2.
[0330] (Example 49)
[0331] In Example 49, a fully solid-state battery was produced in the same manner as in Example 22, except that the outer packaging sheet and the outer packaging paste were prepared by adding 3.2 vol% of sucrose by volume, and the stacking and cutting were performed to form a stacked block, and then the stacking block was washed with ion exchange water for 5 minutes. The porosity P and the self-discharge rate of the outer packaging are shown in Table 2.
[0332] In the all-solid batteries prepared in Examples 25 to 49, all-solid batteries with higher self-discharge characteristics can be obtained by controlling the porosity P. In particular, the all-solid batteries of Examples 25 to 46 can reduce the self-discharge rate compared to the all-solid batteries of Examples 47 to 49 by setting the porosity P to be less than 0.4.
[0333] [Table 2]
[0334]
[0335] Industrial Applicability
[0336] As described above, the all-solid-state battery of the present invention is effective in improving the self-discharge characteristics, which is of great help in the fields of energy and electronics.
Claims
1. An all-solid-state battery, wherein: have: A positive electrode layer comprising a positive electrode current collector layer and a positive electrode active material layer disposed on the positive electrode current collector layer; A negative electrode layer comprising a negative electrode current collector layer and a negative electrode active material layer disposed on the negative electrode current collector layer; as well as a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer and comprising a solid electrolyte, The all-solid-state battery comprises a power storage unit, an exterior unit, and a terminal electrode unit, wherein the positive electrode layer and the negative electrode layer in the power storage unit are opposed to each other via the solid electrolyte layer. The exterior portion is arranged so as to cover the power storage portion except for a portion connected to the terminal electrode. The ionic conductivity of the outer casing is 10 -2 S / cm or less, The outer casing is at least one selected from oxides, phosphates, sulfides and polyanion compounds, and is made of a material whose crystal structure can be identified using an X-ray diffraction pattern. A ratio Y of the ionic conductivity of the outer casing to the ionic conductivity of the solid electrolyte layer is 0≤Y<1, where Y=ionic conductivity of the outer casing / ionic conductivity of the solid electrolyte layer.
2. The all-solid-state battery according to claim 1, wherein: The ratio Y of the ionic conductivity of the outer casing to the ionic conductivity of the solid electrolyte layer is 10 -6 ≤Y<1, where Y=ionic conductivity of the outer casing / ionic conductivity of the solid electrolyte layer.
3. The all-solid-state battery according to claim 1 or 2, wherein: The oxides are oxides of alloys.
4. The all-solid-state battery according to claim 1 or 2, wherein: The exterior portion constitutes at least a portion of the all-solid-state battery excluding the power storage portion.
5. The all-solid-state battery according to claim 1 or 2, wherein: The electronic conductivity of the outer shell is 10 -9 S / cm or less.
6. The all-solid-state battery according to claim 1 or 2, wherein: The porosity P of the outer packaging portion is 0.4 or less.
Citation Information
Patent Citations
Method and system for producing asphalt mixture
JP2013508577A
All-solid type secondary battery
JP2016066550A
Golf ball
JP2018051192A
Secondary battery and its manufacturing method
JP2003092092A
Solid battery and battery pack using the same
JP2016001601A